AROMATERAPI PEPERMINT MENURUNKAN KEJADIAN MUAL DAN MUNTAH PADA PASIEN POST OPERASI - Supatmi Supatmi; Agustiningsih Agustiningsih (Jurnal Kesehatan Karya Husada, 2014)
Surgery with general anesthesia can cause complication afterward. One of thecomplications is nausea and vomiting. Pharmacology and non-pharmacology therapy canbe given to ease nausea and vomiting. Aromatherapy is one of the non-pharmacologytherapies for nausea and vomiting. This study is aimed to determine the duration efectiveof aromatherapy on nausea and vomiting of post-surgery patient with general anesthesia.This is quasi experiment post test-only non equivalent control group. Samples consist of26 respondents on each group. Bivariate analysis shows significant different on nauseaand vomiting between intervention one, intervention two and control groups, wherenausea and vomiting lower on intervention group (p=0,014). It is suggested thataromatherapy can be considered as one of complementary therapy to decrease nausea andvomiting on post-surgery patient.